Modlitwa w Dziejach Apostolskich - Burda, Witold (Verbum Vitae, 2012)
The present study aims at presenting the role of prayer in the life of the early Church the Acts of the Apostles. First, the practice of prayer in the early Church was discussed. In light of the analysis, prayer appears as a fixed practice among the fi rst Christians. The author of the Book of Acts underscores its basic characteristics, to wit faithfulness, perseverance, and unanimity. Second, the places of gathering for prayer were discussed. As many texts from Acts revealed, besides the Jerusalem temple, the private houses were the primary places of gatherings and prayer for early Christians. Third, different approaches and forms which characterized early Christian prayer were revealed. In the final threefold part of this study, the most salient features of prayer were discussed in detail: (1) the prayer of petition, connected in particular way with the gift of the Holy Spirit; (2) the prayer uttered at some crucial moments of the history of the early Church; Luke wanted to show how the first Christians faithfully followed the lead of Jesus, the master of prayer, in their search for God’s will revealed to them in prayer; and (3) the prayer of worship and thanksgiving.